Biobutanol production from cassava waste residue using Clostridium sp. AS3 in batch culture fermentation. Issue 10 (26th November 2021) - Johnravindar, Davidraj; Elangovan, Namasivayam; Gopal, Nellaiappan Olaganathan; Muthaiyan, Arunachalam; Fei, Qiang
Abstract: Tapioca starch factories generate a large amount of wastewater and solid waste, which take several steps of waste treatment to manage. The solid waste contains high level of starchy lignocellulosic materials, especially cassava pulp (CP). The cassava waste residue (CWR) is a potentially promising substrate for the production of biobutanol. Clostridium sp. strain AS3 isolated from a cassava waste processing industrial site utilised a wide range of carbohydrate substrates in a pre-optimised CWR medium. The biobutanol production capacity of the strain was assessed under test conditions of 5% butanol tolerance, pH 6.3, CWR 60 g L −1, pre-treatment acid hydrolysis, inoculum volume 5% v/v, temperature 33 °C, flow rate 0.8 L/L/min, agitation 85 rpm and incubation time 72 h, in serum bottles and also in 5-L reactors for possible scale-up. The results showed that the strain produced 10.5 g L −1 of acetone–butanol–ethanol at a 1:4:11 ratio (v/v/v) from CWR. In subsequent scale-up, the strain produced 0.11 g/L/h of biobutanol that was 70% total solvents produced from CWR. Overall, the batch study showed promising results that the CWR was potentially valorised by solventogenic Clostridium sp. AS3, and this strain has the potential for continuous biobutanol production.